F ( x ) = f ( x ) g ( x ) h ( x )
The above equation is true for all real x , where f ( x ) , g ( x ) and h ( x ) are differentiable functions at some point a .
Given F ′ ( a ) = 2 1 F ( a ) , f ′ ( a ) = 4 f ( a ) , g ′ ( a ) = − 7 g ( a ) , h ′ ( a ) = k h ( a ) . Find k .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
( u v w ) ′ = u ′ v w + u v ′ w + u v w ′
F ′ ( a ) = f ′ ( a ) g ( a ) h ( a ) + f ( a ) g ′ ( a ) h ( a ) + f ( a ) g ( a ) h ′ ( a )
Substituting f ′ ( a ) , g ′ ( a ) , h ′ ( a ) ,
2 1 F ( a ) = f ( a ) g ( a ) h ( a ) [ 4 − 7 + h ] 2 1 = h − 3 ⇒ h = 2 4
F(x) = f(x)g(x)h(x)
F'(x) = f'(x)g(x)h(x) + f(x).( g'(x)h(x) + g(x)h'(x) )
21F(x) = 4f(x)g(x)h(x) + f(x) ( -7g(x)h(x) + k.g(x)h(x) )
21F(x) = ( 4 - 7 + k ).f(x)g(x)h(x)
21F(x) = ( k - 3 )F(x)
k - 3 = 21
k = 24
Problem Loading...
Note Loading...
Set Loading...
We use logarithmic differentiation: take log to both sides of the equation, then differentiate them with respect to x .
ln F ( x ) F ( x ) F ′ ( x ) F ( a ) F ′ ( a ) 2 1 k = = = = = ln ( f ( x ) ) + ln ( g ( x ) ) + ln ( h ( x ) ) f ( x ) f ′ ( x ) + g ( x ) g ′ ( x ) + h ( x ) h ′ ( x ) f ( a ) f ′ ( a ) + g ( a ) g ′ ( a ) + h ( a ) h ′ ( a ) 4 − 7 + k 2 4